Smart battery cell monitoring with contactless data transmission - Lorentz, Vincent; Wenger, Martin; Giegerich, Martin; Zeltner, Stefan; März, Martin; Frey, Lothar (16th International Forum on Advanced Microsystems for Automotive Applications, AMAA 2012, 2012)
The market breakthrough of electric vehicles is mainly delayed by the still too high costs of the battery system. The smart battery cell monitoring presented in this article enables further cost reduction. It consists of battery cells integrating the monitoring electronics together with a data transfer interface for communicating in a bidirectional way with the battery management system. The data transfer interface presented in this paper is based on a differential contactless data transmission bus using galvanically isolated, capacitively coupled links to each single smart battery cell. Since neither galvanic contacts nor connectors are needed, the proposed concept provides simultaneously a very high level of reliability and robustness, and a highly cost-efficient manufacturing process, thus allowing a significant reduction of the final battery pack costs. This paper describes a possible implementation of such a differential contactless data transmission for monitoring and managing battery cells in electric vehicles.
Keywords: Battery management system; Capacitive coupling; Differential bidirectional data transmission bus; Distributed battery monitoring; Smart battery cells